Implementasi Manajemen Kantor Urusan Agama (KUA) Kecamatan Medan Petisah dalam Pembinaan Bimbingan Pra Nikah - Sulidar Sulidar; Tutia Rahmi; Nabila Suharso (ISLAMIKA, 2023)
The purpose of this research is to find out the management of pre-marital counseling guidance at the Medan Petisah Religious Affairs Office (KUA) using a qualitative descriptive method, where data is collected based on interviews, observations made at the Medan Petisah Religious Affairs Office (KUA) on November 18 2022 to December 8, 2022. The implementation or application of management of pre-marital guidance development carried out by the Office of Religious Affairs (KUA) of Medan Petisah District has been carried out in several ways by registering as a person who will carry out a marriage which in this case can be done with an online system so that the implementation process is more effective and efficient, an explanation of marriage and the duties of husband and wife carried out by the KUA so that the bride and groom can build a family that has a strong foundation, religious knowledge about the pillars of Islam, the pillars of faith, memorizing prayers and thaharah so that p The marriage that is carried out does not run away from Islamic religious teachings, guidance on reading the marriage contract so that the prospective groom has preparations when he wants to say the consent qabul.